Price to pay; Portal vein arterialization for hepatic artery thrombosis after living donor liver transplantation; A case report - Lapisatepun, Worakitti (Int J Surg Case Rep, 2018)
OBJECTIVE: Hepatic artery thrombosis (HAT) is one of the most serious complications of liver transplantation that can potentially lead to loss of the allograft. Retransplantation is the only option when revascularization can’t be performed but the donor may be not available in the short period of time. We report the technique of using portal vein arterialization (PVA) for bridging before retransplantation. There are few reports in living donor setting. CASE DESCRIPTION: The recipient of the liver was a 59 year old male who received an extended right lobe graft from his son. Post operative day 41, HAT was diagnosed from angiogram and liver function got rapidly worse. We decided to re-anastomose the hepatic artery but this was not possible due to a thrombosis in the distal right hepatic artery. So PVA by anastomosis of the common hepatic artery to splenic vein was performed. During the early postoperative period liver function gradually improved. Unfortunately, he died from massive GI hemorrhage one month later. DISCUSSION: PVA has previously been reported as being useful when revascularization was not successful. The surgical technique is not complicated and can be performed in sick patient. Liver graft may be salvaged with oxygenated portal flow and recover afterwards. However, portal hypertension after PVA seem to be an inevitable complication. CONCLUSIONS: PVA may be a bridging treatment for retransplantation in patients whom hepatic artery reconstruction is impossible after HAT. Regards to the high morbidity after procedure, retransplantation should be performed as definite treatment as soon as possible.